2011
DOI: 10.1021/jp2033627
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Insulin–Phosphatidylcholine Mixed Langmuir Monolayers: Behavior at the Air–Water Interface

Abstract: The behavior of the binary mixed Langmuir monolayers of bovine insulin (INS) and phosphatidylcholine (PC) spread at the air-water interface was investigated under various subphase conditions. Pure and mixed monolayers were spread on water, on NaOH and phosphate-buffered solutions of pH 7.4, and on Zn(2+)-containing solutions. Miscibility and interactions between the components were studied on the basis of the analysis of the surface pressure (π)-mean molecular area (A) isotherms, surface compression modulus (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…The Insulin monomer is unstable and tends to macroscopically aggregate in aqueous solutions during storage [16,13,6]. This is a consequence of solid fibers formed by aggregation of monomers and dimers under low pH conditions [32,30]; and causes loss of hormone biological activity which is a major obstacle for developing long-term delivery formulations. Though the mechanism of aggregation of Insulin still remains unclear, some studies suggested that the presence of different hydrophobic environments (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Insulin monomer is unstable and tends to macroscopically aggregate in aqueous solutions during storage [16,13,6]. This is a consequence of solid fibers formed by aggregation of monomers and dimers under low pH conditions [32,30]; and causes loss of hormone biological activity which is a major obstacle for developing long-term delivery formulations. Though the mechanism of aggregation of Insulin still remains unclear, some studies suggested that the presence of different hydrophobic environments (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin Langmuir monolayers at the air/water interface were previously described under different experimental conditions such as pH, temperature and ion concentration [29,32,24]. Also, it has been recently shown that the presence of Zn 2+ has a profound effect on the surface behavior of Insulin monolayers [32,24,20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations